IMPLEMENTATION OF EDUCATIONAL PROGRAMS FOR CHILDREN UNDER CARE AT THE CHILDREN’S SPECIAL DEVELOPMENT INSTITUTION CLASS II BANDAR LAMPUNG - Rahman, Muhammad Aulia; Rifani, Denny Nazaria (Universitas Nusa Cendana, 2025)
This study aims to evaluate the implementation of educational programs for juvenile inmates (Andikpas) at the Class II Special Child Development Institute (LPKA) in Bandar Lampung. The educational program at LPKA includes both formal and non-formal education designed to meet the educational rights of children in conflict with the law (ABH). The method used is descriptive qualitative research, with data collected through interviews, observations, and documentation. The results indicate that the participation rate of Andikpas in educational programs is still low, with less than 15% of children attending formal education. The Special Child Correctional Institution (LPKA) plays a crucial role in providing education to children involved in the criminal justice system. The educational programs at LPKA are specifically designed to meet the educational needs and developmental requirements of children of varying ages and levels of need. The main objective is to help these children acquire the knowledge, skills, and understanding necessary for self-improvement and building a better future. Overall, education at LPKA aims not only to provide knowledge and skills but also to help children understand and address the problems they may face, preparing them to reintegrate into society as better and more productive members. The main challenges include a lack of qualified educators, inadequate educational facilities, and low motivation among Andikpas. This research suggests the need for improvements in educational facilities, the provision of qualified teaching staff, and increased support from families and communities to enhance the effectiveness of the educational programs. Keywords: Incarcerated Children; LPKA; Education; Development